ВЛИЯНИЕ ОРОШЕНИЯ НА ВИДОВОЙ СОСТАВ И ЧИСЛЕННОСТЬ ПОЗВОНОЧНЫХ ЖИВОТНЫХ - Фундукчиев , С.Э. (Actual problems and prospects of the study of the fauna, 2024)
Water has determinant significance for development of economy, especially in the hot climate conditions. The drainage water, which shapes fy irrigation; has strong influence on surroundings. Both this changes and direct influence of irrigation on animals cause deep qualitative and quantitative displacement on population and distribution of birds.